Assessment and evaluation in music therapy: is there a difference?. Issue 1 (1st June 2016) - Spiro, Neta; Tsiris, Giorgos
Abstract : Background : As the music therapy profession and discipline has grown, more and more studies have explored whether and how music therapy works within different settings and with different client groups. These studies vary not only in terms of their methods, but also in terms of their overall focus, function and methodological framework. As a result, a number of research, evaluation and outcome assessment initiatives have been developed. Despite their different functions, however, the terms research, evaluation and assessment have, at times, been used interchangeably. Objective and Methods : The aim of this presentation is to explore these terms with a particular focus on assessment and evaluation. This exploration is based on our long-term evaluation work of Nordoff Robbins music therapy services and on a recent review of outcome assessment measures in music therapy. Conclusions and Discussion : This presentation will hopefully contribute to a systematic understanding of assessment and evaluation, as well as of their distinct functions and their relationship to research. On the basis of practical examples, this presentation will point towards a potential conceptual framework and the development of approaches to assessment and evaluation and their various uses in practice.